Case study of a Brazilian community association : a thesis presented in partial fulfillment of the requirements for the degree of Master in Public Policy at Massey University, Auckland, New Zealand - Rocha, Alberto Frederico Moraes da (Massey University, 2007)
This is a Case Study Research done inside a poor community in Brazil. The main goal of the research is to facilitate this community to understand their problems and to overcome it. Therefore the researcher and the researched developed the following question ‘why NovaMosanta is not achieving its goals? The researcher wanted to work as a facilitator throughout the whole process of dialogue that aims to empower the community. Departing from that question and based on Freire’s ideas of education the research aims to build new knowledge from the interaction of academic and community knowledge. To implement this case study field research the researcher decided to use Participant observation and questionnaires. Surprisingly during the research the NGO called NovaMosanta faced the challenge of remodeling a public school without government help; otherwise the school would be closed. This NGO succeeded with the help of the New Zealand Government that gave NZ$15,000 to build two new classrooms in the school. Community members helped working in the remodeling and local commerce gave discounts to enable the remodeling. As a result the school will not be closed and the students will continue to study there. It also helped to increase community support and participation. Although not designed as a Participant Action Research, this thesis evolved to produce action and to change the community reality. It was an empowering process to the researcher and the researched. The community support increased and it also served s a catalytic event in the process of transformation and inclusion. Finally it clarifies the importance of producing fast results to maintain community support. You can check the research results in the links below that contain two local network reports about it. (http://www.youtube.com/watch?v=Hz_FItXp3nM) & (http://www.youtube.com/watch?v=py5emCNXRlo)
Keywords: Non-governmental organisations; Community participation; Community support; Public schools; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy